Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Pegawai Badan Penelitian Dan Pengembangan Daerah Kabupaten Tulang Bawang - Sinaga, Tiar Melda Sari Octaviana; Josiah, Trisnowati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Strong resources and optimal Human Resources (HR) are essential for organizations to achieve their goals and face competition. Employee performance significantly impacts organizational success, as seen in the Research and Development Agency (Balitbangda) of Tulang Bawang Regency, where work discipline and motivation are key factors. Observations indicate that low employee discipline, characterized by tardiness and absenteeism, along with low motivation due to insufficient rewards and adequate facilities, hinder performance. This study aims to examine the influence of work discipline and motivation on the performance of Balitbangda employees, with the expectation of generating recommendations for performance improvement and the organization's contribution to regional development. Research methods involve scientific approaches to obtain data for specific purposes, conducted rationally, empirically, and systematically. This study was conducted at the Research and Development Agency of Tulang Bawang Regency using a descriptive quantitative approach, aiming to accurately describe facts and characteristics of the population. The research population consists of 27 civil servants, with a sample of 26 respondents after the researcher was excluded from the sample. The research variables include work discipline (X1) and motivation (X2) as independent variables, and employee performance (Y) as the dependent variable. The results of this study indicate that work discipline has a significant effect on the performance of Balitbangda employees, contributing 21.3%, thus accepting the first hypothesis. Additionally, motivation also has a significant impact on employee performance, contributing 11.1%, thereby accepting the second hypothesis. Overall, work discipline and motivation together contribute 54.1% to employee performance, while the remaining 45.9% is influenced by other factors not examined in this study.